Development of thermoplastic vulcanizates based on polypropylene/ethylene propylene diene monomer for prototyping by Fused Filament Fabrication. (24th April 2023) - Innes, J.R.; Shriky, B.; Nocita, D.; Thompson, G.; Coates, P.; Whiteside, B.; Kelly, A.; Hebda, M.
Abstract: This article demonstrates how thermoplastic vulcanizates (TPVs) can be 3D printed by modifying their formulation and the Fused Filament Fabrication (FFF) process. Novel FFF filaments based on polypropylene (PP)/ethylene propylene diene monomer (EPDM) blends were printed and characterized. The development of these TPV filaments allows a broad range of properties by varying the grades of the thermoplastic/rubber phases. Thermoplastic vulcanizates are widely used in the automotive industry, amongst others, and a printable filament could have applications in both prototyping and production of bespoke parts. Given the increasing prominence of TPVs, as replacement for thermoset rubbers, FFF of these materials is considered industrially beneficial. The newly prepared TPVs possessed tensile strength of ∼20–30 MPa and elongation at break ∼700–1100% when measured in the direction of printing. Tensile properties (at 0° and 90° to the printing direction), interlayer adhesion, and Micro-CT were measured and compared with neat PP and PLA. Graphical abstract: Image 1 Highlights: Thermoplastic vulcanizates based on PP and EPDM were successfully 3D printed and compared with neat PP and commercial PLA. The elongation at break of these TPVs far exceeds the values achieved by PP and PLA and even commercial TPU filaments. The low void content of the prepared TPVs suggests that wetting and infill were not problematic for these novel filaments.